Analysis of Fatwas by the National Sharia Board-Indonesian Council of Ulama on the Stock Market - Yuli Andriansyah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
This research aims to analyze the fatwas issued by the National Sharia Board-Indonesian Council of Ulama (Dewan Syariah Nasional Majelis Ulama Indonesia, abbreviated DSN-MUI in Bahasa Indonesia) concerning activities in the stock market. This study focused on the characteristics and general development of these fatwas. This study adopts a normative approach to examine whether the DSN-MUI fatwas related to the stock market. The data utilized in this study are of a secondary nature, encompassing fatwa information issued by the DSN-MUI. These data were further analyzed using a descriptive-qualitative approach and content analysis, particularly pertaining to fatwas. The results of this research indicate that the fatwas issued by the DSN-MUI serves varying purposes across different periods. These fatwas sometimes emerge as responses to questions about business matters or as reactions to recent developments in stock market products. Another finding of this study is that the fatwas issued by the DSN-MUI followed a specific pattern in its structure, starting with verses from the Quran and Hadith of the Prophet, followed by Fiqh principles, opinions of classical and contemporary scholars, and concluding with the National Sharia Board's stance on the specific topic. The development of these fatwas reflects the gradual (tadarruj) principle within Islamic jurisprudence regarding legal action.